2022
DOI: 10.1007/978-3-031-05061-9_17
|View full text |Cite
|
Sign up to set email alerts
|

Behind the Scenes: Exploring Context and Audience Engagement Behaviors in YouTube Vlogs

Abstract: Famous video bloggers (vloggers) on YouTube can develop large audiences, which can be related to the gaining of audience engagement (AE), manifested by the viewers' participation and consumption on YouTube. Studies have unveiled vloggers' behaviors for engaging audiences, or audience engagement behaviors (AEBs), in their videos, including interacting with viewers via comments, disclosing self-information, giving rewards, and offering other information. Meanwhile, video blogs (vlogs) are produced under "vloggi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Previous research uncovered creators' behaviors for audience engagement on YouTube including the use of comment sections for participation [11][12][13] and fulfilling viewers' needs of seeking information [14] by, for example, using descriptions on YouTube. Our research added to those studies and found that YouTubers also try to utilize similar features on Bilibili when cross-posting to engage their viewers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research uncovered creators' behaviors for audience engagement on YouTube including the use of comment sections for participation [11][12][13] and fulfilling viewers' needs of seeking information [14] by, for example, using descriptions on YouTube. Our research added to those studies and found that YouTubers also try to utilize similar features on Bilibili when cross-posting to engage their viewers.…”
Section: Discussionmentioning
confidence: 99%
“…Policymakers and businesses can nudge consumers toward energy-efficient choices by employing interventions informed by behavioral economics, such as financial incentives and real-time energy usage data. Y. Zhang et al [44] delve into the issue of energy consumption and its impact on environmental challenges, highlighting the willingness of consumers to pay a premium for energy-saving appliances. Their study identifies key factors influencing consumer attitudes, perceived quality, price, and emotional and environmental values, shedding light on strategies to promote the adoption of energy-saving appliances.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, famous YouTubers, who have obtained large fan bases on YouTube also use Twitter to connect with their viewers. YouTubers were found to have ways to engage their audience within YouTube, such as interacting with viewers through video comments and sharing personal stories in videos (Zhang, 2022). However, using Twitter was found to be a part of their self-branding process (Tarnovskaya, 2017) beyond the YouTube platform.…”
Section: Introductionmentioning
confidence: 99%